Macroeconomic fluctuations in a stylized DSGE model with disequilibrium dynamics - Bas van Aarle (Center for Economic Studies and ifo Institute (CESifo), 2012)
This study develops a stylised DSGE model, that departs in one aspect: it replaces the general equilibrium approach by disequilibrium economics. In this way, richer macroeconomic adjustment dynamics result, as it is not necessary to assume that goods and labour markets continuously clear. The disequilibrium dynamics - in the form of regime-dependent output and employment fluctuations, wage and price adjustments-complicate (viz. enrich) the decision making problems faced by the fiscal and monetary policymakers. In particular the possibility of (multiple) regime switches implies the need for deeper analysis and monitoring of the disequilibrium mechanisms when designing and implementing monetary and fiscal policies.
Keywords: C22; E32; E66; F42; 330; disequilibrium analysis; DSGE model; macroeconomic policy